2016
DOI: 10.1038/ncb3420
|View full text |Cite
|
Sign up to set email alerts
|

Amnioserosa cell constriction but not epidermal actin cable tension autonomously drives dorsal closure

Abstract: Tissue morphogenesis requires coordination of multiple force-producing components. During dorsal closure in fly embryogenesis, an epidermis opening closes. A tensioned epidermal actin/MyosinII cable, which surrounds the opening, produces a force that is thought to combine with another MyosinII force mediating apical constriction of the amnioserosa cells that fill the opening. A model proposing that each force could autonomously drive dorsal closure was recently challenged by a model in which the two forces com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 53 publications
7
109
0
1
Order By: Relevance
“…S4B). These results are similar to the ones obtained by the striped expression of a dominant-negative version of Rho1, which is a positive upstream regulator of MyoII (Jacinto et al, 2002), and corroborate two more recent studies using either loss-of-function mutants or deGradFP to disrupt the leading edge actomyosin cable (Ducuing and Vincent, 2016;Pasakarnis et al, 2016). Finally, knockdown of Sqh-GFP in stripes resulted in embryonic lethality in male embryos, while female embryos, which carry a wild-type sqh copy, gave rise to viable progeny ( Fig.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…S4B). These results are similar to the ones obtained by the striped expression of a dominant-negative version of Rho1, which is a positive upstream regulator of MyoII (Jacinto et al, 2002), and corroborate two more recent studies using either loss-of-function mutants or deGradFP to disrupt the leading edge actomyosin cable (Ducuing and Vincent, 2016;Pasakarnis et al, 2016). Finally, knockdown of Sqh-GFP in stripes resulted in embryonic lethality in male embryos, while female embryos, which carry a wild-type sqh copy, gave rise to viable progeny ( Fig.…”
Section: Introductionsupporting
confidence: 78%
“…S3B, arrowheads). This observation was similar to what was previously reported in the epidermis (Pasakarnis et al, 2016) and the wing imaginal discs (Caussinus et al, 2012). Live imaging of the F-actin reporter Lifeact-Ruby revealed that Sqh-GFP knockdown males formed thicker and longer filipodia at the leading edge than the control embryos (compare Fig.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations